Faktor-faktor yang Mempengaruhi Nilai Perusahaan Subsektor Konstruksi - Dhea Zatira; Titis Nistia Sari (FEB Universitas Sultan Ageng Tirtayasa, 2020)
This study aims to examine the effect of Profitability, Debt Policy, Dividend Policy, and Investment Decisions on the Value of firms in the Construction subsector listed on the Indonesia stock exchange in the period 2015-2018. The data analysis technique used in this study is a multiple regression model with E-Views software. The object used is the construction subsector company and is the strongest sector in economic development in Indonesia. The building and construction sector occupies the third position as the main source of economic growth in Indonesia. The test results prove that profitability and investment decisions affect the value of firms. While the Debt Policy and Dividend Policy do not affect on the Value of firms. Simultaneously Profitability, Debt Policy, Dividend Policy, and Investment Decisions can explain the Value of firms of 33.673%, while the remaining 66.371% is explained by other variables not examined in this study.